(untitled) (Bangladesh Journal of Medical Science, 2017)
Background: Doxorubicin chemotherapy may induce the development of resistance in the cancer cells. Overexpression of P-glycoprotein (P-gp) has prominent causative role in this process. Unfortunately, many inhibitory agents do not exert satisfying clinical outcome to overcome resistance. Quercetin, a polyphenolic compound, can be developed as P-gp inhibitor due to its cytotoxic properties. Objective: To investigate the effect of quercetin and doxorubicin combination in inhibiting the development of resistance in MCF-7 cell. Methods: Doxorubicin resistant MCF-7 cell were developed from the parent MCF-7 cell by exposing to 75 nM doxorubicin for 25 days. The inhibitory effect of resistance was evaluated via exposured to 75 nM doxorubicin and 750 nM quercetin combination in the same manner with resistance induction. MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide) citotoxicity assay and flowcytometry assay were performed to investigate the degree of resistance and to inhibit the development of resistance. Results: The exposure of 75 nM doxorubicin in MCF-7 cells (MCF-7 cells/dox75) exhibited sensitivity significantly decrease and upregulation of P-gp expression. The combination of 750 nM quercetin and 75 nM doxorubicin (MCF-7 cells/ dox75q750) caused a significantly increase in cell sensitivity to doxorubicin (p<0,05) and a decrease in P-gp expression (p> 0,05). Conclusions: The exposure of 75 nM doxorubicin led to the development of doxorubicin-acquired resistance MCF-7 cell. The combination of quercetin and doxorubicin have potency to inhibit the development of doxorubicin-acquired resistance MCF-7 cell by increasing cell sensitivity and reducing P-gp expression level. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.91-97